Estimation on Rational Speculative Bubbles in Stock Market by using Generalised Johansen-ledoit-sornette Model - Borhan, N.; Halim, N. A. (Penerbit Universiti Putra Malaysia (UPM Press), 2024)
Indexed by Scopus/MyCite